2021
DOI: 10.1016/j.sjbs.2021.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Determination of synergistic effects of antibiotics and Zno NPs against isolated E. Coli and A. Baumannii bacterial strains from clinical samples

Abstract: The mortality rates has been increased globally due to multidrug resistant (MDR) E.coli and A.baumanii bacterial strains and also there is an emerging resistance of the Enterobacteriaceae family of bacteria to Carbapenem antibiotics (CRE) in Saudi Arabia. The main aim of our research study is to isolate E.coli and A. baumannii bacterial species from various collected clinical samples and to evaluate the MIC and FICI of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…These phenomena demonstrated that both new salts reduced the MIC value of LF by two-fold in the pH 6.8 and 7.4 media for the tested strains. The increase in antimicrobial effect may be supported by the synergic work of 2,6-DHBA and 3,5-DHBA with LF, which was confirmed by measuring their FΣFICI [ 42 ]. Prior research reported that both compounds have a minor potency toward S. aureus and E. coli with MIC values of 2 mg/mL and 3 mg/mL, respectively [ 25 ].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These phenomena demonstrated that both new salts reduced the MIC value of LF by two-fold in the pH 6.8 and 7.4 media for the tested strains. The increase in antimicrobial effect may be supported by the synergic work of 2,6-DHBA and 3,5-DHBA with LF, which was confirmed by measuring their FΣFICI [ 42 ]. Prior research reported that both compounds have a minor potency toward S. aureus and E. coli with MIC values of 2 mg/mL and 3 mg/mL, respectively [ 25 ].…”
Section: Resultsmentioning
confidence: 97%
“…The combined effect was calculated using the fractional inhibitory concentration index (FICI) equation. ΣFICI value represented the synergy effect ≤0.5, while the indifferent and antagonist results were indicated by ΣFICI value >0.5 to <2 and ΣFICI value ≥2, respectively [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting that this combination also exhibited a remarkable correction in the clinical picture of MG and/or ORT experimental infections in chickens indicating that the use of aivlosin/ZnO-NPs treatment is successful in combating these clinical infections in the field. A recent study investigated the synergistic effects of ZnO-NPs and various antibiotics combinations against some Gram negative clinically bacterial isolates ( Fadwa et al., 2021a , Fadwa et al., 2021b ,). This success could be attributed to the combination of both therapies with their different modes of actions.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between the investigated compounds was assessed via calculating the fractional inhibitory concentration index (FICI) according to the following equation: FICI = MIC of aivlosin in combination/MIC of aivlosin alone + MIC of ZnO-NPs in combination/MIC of ZnO-NPs alone. The results were interpreted as following: synergism (FICI ≤ 0.5), additivity (0.5 < FICI ≤ 1), indifference (1 < FICI ≤ 4) and antagonism (FICI > 4) ( Fadwa et al., 2021a , Fadwa et al., 2021b ).…”
Section: Methodsmentioning
confidence: 99%
“…It was proposed that active groups in the antibiotic molecule, such as hydroxyl and amido, reacted with the nanosized metallic copper by chelation, and the reaction led to synergism. Synergistic antibacterial effects were observed for silver and copper HNCs with the antibiotics tetracycline and kanamycin against the biorecycling microbes Bacillus subtilis and Pseudomonas fluorescens [ 145 ]. A group of antibiotics (azithromycin, cefotaxime, cefuroxime, fosfomycin, and chloramphenicol) had a synergistic effect in the presence of ZnO and Ag INPs against Escherichia coli .…”
Section: Nanocomposites Of Inps With Antibacterial Drug Substancesmentioning
confidence: 99%